A STUDY COOPERATIVE PRINCIPLE IN INDONESIAN POLITICAL LANGUAGE - Norwanto, Norwanto (Kajian Linguistik dan Sastra, 2006)
This study scrutinizes Indonesian Political Language from cooperative principle perspective. The object of the study is Indonesian political language in words, phrase, clause, sentence, or discourse taken from Indonesian newspapers. The data was analyzed using Griceâs cooperative principle. The study shows that politicians ex- ploit the maxims of cooperative principles regularly. Politicians violate the maxim of quantity to express strong commitment or hide information. Giving incorrect information violates the maxim of quality to obey quantity maxim. They also vio- late the maxim of relevance by saying things, which are not germane to the topic under discussion.Â Key words: Cooperative Principles, maxims of conversation, and violation.Â